Estudos estruturais com fosfolipases A2 isoladas de venenos de serpentes dos gêneros Bothrops e Crotalus - Fernandes, Carlos Alexandre Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Snakebite is a very serious public health problem still today, affecting tropical and subtropical countries, especially the rural areas of Africa, Asia, Oceania and Latin America. In Brazil, Bothrops and Crotalus snake genus are responsible of almost 90% of snakebites. The venoms of Bothrops snakes have a class of phospholipases A2, known as Lys49-PLA2s, which do not have catalytic activity. However, they are able to induce myonecrosis by a non-catalytic mechanism that is not fully understood. In the venom of Crotalus snakes, a phospholipase A2, known as crotoxin constitutes about 60% of the venom from these animals. This protein is a potent neurotoxin that causes a large block of neuromuscular transmission formed by complexation of crotoxin A (non-catalytic) and crotoxin B (catalytic). In this work, it was used several theoretical and experimental techniques, in particular X-ray protein crystallography, to generate information to extend the knowledge of the action of these proteins. Regarding to crotoxin, the crystal structure of crotoxin B isolated from Crotalus durissus colillinetaus was solved and the heterologous expression of isoform CBa2 of crotoxin B from Crotalus durissus terrificus was performed, in order to, subsequently, produce site-directed mutants. Furthermore, it is presented small angle X-ray scattering experiments with the crotoxin and its isolated subunits that provided intriguing and novel information about the oligomerization of these proteins. Regarding to Lys49-PLA2s from Bothrops snakes, it is presented two new crystal structures of this class isolated from Amazonian snake B. brazili. The analysis of these structures and the structural comparison to other Lys49-PLA2s crystallographic structures generated new information about the position of hydrophobic residues in C-terminal portion of these proteins. This information led us to a new proposition of the mechanism of action of these proteins. It is also presented ...

Ainda nos dias de hoje, o envenenamento ofídico é um problema de saúde pública, afetando sobretudo, regiões de clima tropical, subtropical e áreas rurais de países da África, Ásia, Oceania e América Latina. No Brasil, os gêneros de serpentes Bothrops e Crotalus são responsáveis por quase 90% dos acidentes ofídicos, sendo que os acidentes provocados por este último apresentam relativa alta taxa de mortalidade. O veneno das serpentes do gênero Bothrops possuem uma classe de fosfolipases A2, as Lys49-PLA2s, que não possuem atividade catalítica, mas são capazes de induzir a mionecrose por uma mecanismo não catalítico que não é totalmente conhecido. Com relação às fosfolipases A2 veneno das serpentes do gênero Crotalus, o complexo crotoxina, formado pela crotoxina A (não catalítica) e a crotoxina B (catalítica) pode constituir até cerca de 60% do veneno desses animais, como no caso da subespécie Crotalus durissus terrificus, e é uma potente neurotoxina que provoca um grande bloqueio da transmissão neuromuscular. Neste trabalho, utilizando diversas técnicas teóricas e experimentais, sobretudo cristalografia de raios X, são apresentados diversos resultados que visam aprofundar o conhecimento acerca do funcionamento destas proteínas. Com relação à crotoxina, é apresentado a estrutura cristalográfica da crotoxina B de Crotalus durissus colillineatus, a expressão heteróloga da isoforma CBa2 da crotoxina B de Crotalus durissus terrificus para a posterior produção de formas mutantes sítio-dirigidas e resultados da análise do espalhamento de raios X a baixo ângulo da crotoxina e de suas subunidades isoladas, gerando informações relevantes e inéditas acerca da oligomerização destas proteínas. No caso das Lys49-PLA2s isoladas do veneno botrópico, são apresentadas duas novas estruturas cristalográficas dessa classe de proteínas isolada da serpente amazônica B. brazili. A análise ...
Keywords: Serpente peçonhenta - Genética; Cobra - Veneno; Biologia molecular; Fosfolipases; Molecular biology